PENGARUH EKSPEKTASI LABA TERHADAP MINAT BERWIRAUSAHA (Studi Pada Mahasiswa Angkatan 2013 STIE MBI Jakarta) - Marwan Efendi; Miranti Yudhati (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2017)
This thesis was written by Miranti Yudhati, Nim 13010001, from May 2017 to August 2017, entitled: The Influence of Profit Expectations To Words Doing Business (Study gradued studies years 2013 STIE MBI Jakarta). This study aims to produce information in the form of a more in-depth explanation of the results of data processing about how much influence of earnings expectations on entrepreneur interest. The research method used in this research is the causality and the form of quantitative and qualitative research by using descriptive and verivative type, that is by form of field study and direct survey either through interview or observation in the form of direct observation. Based on the calculation with simple linear regression equation between X and Y is = 29,068 + 0,431X ...... e, this means if there is an increase of expectation of profit 1 point then entrepreneurship interest will increase to equal to 29,068 + 0,431 (1) = 29,499 . While the results of Hypothesis Testing, obtained profit expression variables have a value of sig <0.05 means significant. While tcount = 3.761 and ttable = 2,003. Then variable earnings expectations proved there is a relationship to entrepreneurship interests, so Ho is rejected and Ha accepted. And based on correlation coefficient analysis obtained value r = 0.449 This means there is a strong and positive relationship which indicates that the increase in earnings expectations in general can increase interest in entrepreneurship. While the results of KD (R ^ 2) = 20.2%. It means that 0.2% of the independent variable is the profit expectation can be explained by the dependent variable is entrepreneur interest. While the remaining 79.8% is explained by other factors not examined by this study